Mesh repair versus non mesh repair of primaryinguinal hernia - Al-Obaidi, Safa M.; Al-Sarraf, Salem A.; Salim, Othman A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Techniques of Inguinal hernia repair have seen an evolution from the pure tissue repair to the prosthetic repair and in the recent years past to laparoscopic repair. High recurrence rates using fascia for the hernia repair or the use of sutures under tension prompted the development of polypropylene mesh to reinforce the posterior wall of the inguinal canal.The aim of this study is to compare the post operative results of Lichtenstein mesh technique with Dar ning repair. Patients and methods:-A prospective study of "100" patients with inguinal hernia were conducted to evaluate two methods, of open repair of inguinal hernia Lichtenstein mesh technique with Traditional non-mesh technique (modified Bassini or Darning).Operation were done under general, epidural and local anaesthesia at the surgical units of Baghdad Teaching Hospital and Arbil Teaching Hospital. Results: The study showed that Lichtenstein mesh technique is an effective operation for repair of inguinal hernia with low complication rate and less pain in comparison to the repair by traditional non-mesh technique. Also the results show that, mesh repair group returned to work earlier than non-mesh repair group. Conclusion:Mesh repair of primary inguinal hernia repair is superior to non-mesh repair in term of early postoperative pain , return to the work and recurrence.